FCES, Fellow the Commercial Education Society of Australia (CESA) - Souleles, Nicos (My University, 2026)
Fellowship of the Commercial Education Society of Australia (FCES) is open to people who have distinguished themselves in commercial/business education and/or have a record of support for the Society and its objectives.
Keywords: Education